2022
DOI: 10.3389/fmars.2022.1058839
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of high-frequency dissolved oxygen dynamics in a shallow estuary, the Corsica River, Chesapeake Bay

Abstract: Understanding shallow water biogeochemical dynamics is a challenge in coastal regions, due to the presence of highly variable land-water interface fluxes, tight coupling with sediment processes, tidal dynamics, and diurnal variability in biogeochemical processes. While the deployment of continuous monitoring devices has improved our understanding of high-frequency (12 - 24 hours) variability and spatial heterogeneity in shallow regions, mechanistic modeling of these dynamics has lagged behind conceptual and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The relative importance of resolving high-frequency fluctuations in DOb therefore depends on the duration of hypoxia as well as Ai, which varies as a function of tidal current speed and spatial DOb gradient. Tian et al (2022) similarly showed for the Corsica River estuary that tidal advection accounts for a larger percentage of DO variability at hourly timescales compared to yearly timescales. As shown here, approaches to evaluating continuous and discrete data together are relevant to recent efforts in LIS and other systems (e.g., Chesapeake Bay, Murphy et al, 2019) to develop empirical predictive models for hypoxia.…”
Section: Leveraging Continuous Timeseries Measurements To Improve Est...mentioning
confidence: 77%
See 1 more Smart Citation
“…The relative importance of resolving high-frequency fluctuations in DOb therefore depends on the duration of hypoxia as well as Ai, which varies as a function of tidal current speed and spatial DOb gradient. Tian et al (2022) similarly showed for the Corsica River estuary that tidal advection accounts for a larger percentage of DO variability at hourly timescales compared to yearly timescales. As shown here, approaches to evaluating continuous and discrete data together are relevant to recent efforts in LIS and other systems (e.g., Chesapeake Bay, Murphy et al, 2019) to develop empirical predictive models for hypoxia.…”
Section: Leveraging Continuous Timeseries Measurements To Improve Est...mentioning
confidence: 77%
“…In other estuaries, highfrequency fluctuations in DO have been examined most often in shallow areas, where dielcycling dynamics are typically dominated by diurnal cycles of daytime net production and nighttime net respiration (D'Avanzo and Kremer 1994;Beck and Bruland 2000;Shen et al, 2008). Diel-cycling DO has also been associated with advection and mixing by tides (Simpson et al, 1990;Breitburg, 1990;Tian et al, 2022), and wind-driven mixing associated with sea-breeze dynamics (Duvall et al, 2022). Determining biophysical processes driving high-frequency fluctuations in DO is fundamental to our understanding of water quality dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…This means that there was a physical signal in the DO flux time series. Tian et al (2022) reported significant tidal impact on water quality in shallow water systems, and Kwon et al (2014) observed tidal signals in benthic microalgal production, which ultimately affected DO flux. Tide influences benthic microalgal production mostly through altering environmental conditions, such as temperature, nutrient abundance, water depth, and light availability.…”
Section: Benthic Microalgal Impact On Highfrequency Variability In Do...mentioning
confidence: 99%
“…Electronic sensor-based continuous monitoring often shows high-frequency and large amplitude variability in DO and chlorophyll in shallow water systems (Shen et al, 2008;Graziano and Jones, 2017;Duvall et al, 2022). The understanding and modeling of these large high-frequency variations represent a challenge for the modeling community (Xia et al, 2010;Xia et al, 2011;Xia and Jiang, 2015;Tian, 2019;Tian, 2020;Tian et al, 2022). The objective of this study is to investigate the mechanisms controlling benthic microalgal dynamics and their impact on water quality high-frequency variability in shallow water systems using this fully coupled physical, water quality, and benthic microalga modeling system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation